An application of a noncompactness technique to an investigation of the existence of solutions to a nonlocal multivalued Darboux problem. (1999) - Byszewski, Ludwik; Papageorgiou, Nikolaos S.
Abstract : The aim of the paper is to prove two theorems on the existence of solutions to a nonlocal multivalued Darboux problem. The first theorem concerns the case when the orientor field is convex valued. The second theorem concerns the case when the orientor field is nonconvex valued. A compactness type condition involving the ball measure of noncompactness is applied.